Evaluation of empathy among undergraduate nursing students: a three-year longitudinal study: Evaluation of empathy among nursing students - Ferri, Paola; Rovesti, Sergio; Bonetti, Loris; Stifani, Serena; Panzera, Nunzio; Di Lorenzo, Rosaria (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: An empathic approach is considered fundamental in order to ensure the identification of patient needs and to provide the appropriate care, although the studies on the development of empathic attitude during nursing course reported conflicting results. Different empathic tendencies have been observed in the two genders: many studies showed greater empathy in females. Methods: To assess empathy level of students enrolled in the academic year 2015/16 at an Italian University nursing course, the Balanced Emotional Empathy Scale (BEES) was administered at the start of Year 1 (n=118), at the mid-point of Year 2 (n=99) and at the end of Year 3 (n=67). Data were statistically analyzed. Results: Cronbach’s values were satisfactory (0.87 at Year 1, 0.89 at Year 2, 0.79 at Year 3), confirming the good internal reliability of BEES. The nursing students obtained a total BEES mean ± SD score of 37.0 ± 19.5 at Year 1, 33.5 ± 22.6 at Year 2 and 35.4 ± 16 at Year 3, without any statistically significant difference among the three years. The BEES mean scores reported by males were lower in comparison with females during the three years of the course, although, at the end of the third year, males showed a significant increase at the “Emotional spread responsiveness” dimension of the scale. Conclusions: The study suggests that empathy can be maintained at good levels during the nursing education especially if nursing teaching and internship are focused on this topic, acting up the innate aptitude of each student.